Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae) - Zhang, Chao; Zhang, Feng; Sharma, Prashant P. (Zootaxa, 2018)
Two new species of Petrobunus Sharma & Giribet, 2011, (Petrobunidae) are described: P. chongqing sp. nov. (♀♂) and P. hebei sp. nov. (♀♂). Petrobunus chongqing sp. nov. is similar to P. spinifer Sharma & Giribet, 2011, in having two large spines on the male sternite 7. However, the new species can be distinguished from P. spinifer by the absence of a ventral tubercle on the male femur IV, as well as the presence of three pairs of enlarged tubercles on the lateral margin of area V and free tergites I–II. Petrobunus hebei sp. nov. and P. torosus Sharma & Giribet, 2011 closely resemble each other. They are distinguished by the morphology of the ocularium, in that P. torosus has a median tubercle whereas the ocularium of P. hebei sp. nov. is unarmed. The discovery and descriptions of these species greatly expand the known range of the genus Petrobunus.